2017
DOI: 10.5296/ajfa.v9i2.12229
|View full text |Cite
|
Sign up to set email alerts
|

Use of Capital Investment Appraisal Practices and Effectiveness of Investment Decisions: A Study on Listed Manufacturing Companies in Sri Lanka

Abstract: Primary objective of the present study was to examine the relationship between use of capital investment appraisal practices and effectiveness of investment decision of listed manufacturing companies in Sri Lanka. Capital investment appraisal practices were measured by capital investment appraisal techniques and risk analysis techniques of investment projects. Effectiveness of investment was measured by perceptions of CFOs on the performance from investment. Firm size was used as the control variable to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…In the context of Romania, CSR has grown in interest in recent years, noting that the companies involved in these projects invest a considerable amount (Grabara et al, 2016). At the same time, there is a relationship between capital investment and decisions taken, which is crucial when carrying out CSR initiatives (Kengatharan & Clamenthu, 2017).…”
Section: Recent Issues In Economic Developmentmentioning
confidence: 99%
“…In the context of Romania, CSR has grown in interest in recent years, noting that the companies involved in these projects invest a considerable amount (Grabara et al, 2016). At the same time, there is a relationship between capital investment and decisions taken, which is crucial when carrying out CSR initiatives (Kengatharan & Clamenthu, 2017).…”
Section: Recent Issues In Economic Developmentmentioning
confidence: 99%
“…SMEs internal characteristics in relation to their growth, performance and investment decisions have been adequately researched (Kazimoto, 2014;Farsi & Toghraee, 2014;Bouazza, Ardjouman & Abada, 2015;Quartey, Turkson, Abor & Iddrisu, 2017;Appiah, Possumah, Ahmat, & Sanusi, 2018). For instance, Kengatharan and Clamenthu (2017) determined the relationship between capital investment practices and investment decisions of manufacturing companies. The study found significant and positive relationships between present value, internal rate of return and investment decisions.…”
Section: Internal Firm Characteristics and Investment Decisionsmentioning
confidence: 99%